Relationship of Health Anxiety and Mental Health with Psychological Vulnerability Mediated by Perceived Social Support in Nurses Working in COVID-19 Wards - Mazhari, Rozita; Farhangi , Abdolhassan; Naderi, Farah (Advances in Nursing & Midwifery, 2023)
Introduction: Nurses have a crucial position in health care, making up more than 75% of health care providers. The working environment can cause chronic stress in nurses. The present study aimed to investigate the relationship of health anxiety and mental health with psychological vulnerability mediated by perceived social support in nurses working in COVID-19 wards in Shiraz (Iran). Methods: This descriptive-correlational study used multistage random sampling to enroll all 200 nurses of the COVID unit of the hospital in Shiraz in 2022. The research tools included the General Health Questionaire-28, the Health Anxiety Questionnaire, the Multidimensional Scale of Perceived Social Support, and the Psychological Vulnerability Scale. The proposed model was evaluated using structural equation modeling (SEM). Results: The results showed that the proposed model had a good fit. According to the results the direct paths from perceived social support and mental health to psychological vulnerability were significant (P<0.01). There was a positive and significant relationship between health anxiety with psychological vulnerability and perceived social support with mental health (P<0.01). The direct path from health anxiety to perceived social support was not significant. Conclusions: Mental health and perceived social support effectively reduced psychological vulnerability and could help mitigate the psychological harms caused by the COVID-19 pandemic.